CDKN2A/CDK4 Status in Greek Patients with Familial Melanoma and Association with Clinico-epidemiological Parameters - Fani Karagianni; Ching-Ni Njauw; Katerina P. Kypreou; Aravela Stergiopoulou; Michaela Plaka; Dorothea Polydorou; Vasiliki Chasapi; Leontios Pappas; Ioannis A. Stratigos; Gregory Champsas; Peter Panagiotou; Helen Gogas; et al. (Medical Journals Sweden, 2018)
Approximately 5-10% of melanoma cases occur in a familial context. CDKN2A/CDK4 were the first high-penetrance melanoma genes identified. The aims of this study were to evaluate CDKN2A/CDK4 variants in Greek familial melanoma patients and to correlate the mutational status with specific clinico-epidemiological characteristics. A cross-sectional study was conducted by genotyping CDKN2A/CDK4 variants and selected MC1R polymorphisms in 52 melanoma-prone families. Descriptive statistics were calculated and comparisons were made using the χ2 test, Fisher's exact test and Student's t-test for statistical analysis, as appropriate. CDKN2A variants were detected in 46.2% of melanoma-prone families, while a CDK4 variant was found in only one family. This study confirmed that, in the Greek population, the age at melanoma diagnosis was lower in patients carrying a variant in CDKN2A compared with wild-type patients. No statistically significant associations were found between CDKN2A mutational status and MC1R polymorphisms.